Seasonal variations in the occurrence of preeclampsia and potential implication of upper respiratory infections in South Korea - Eui hyeok Kim; Sang Ah Lee; Seunggi Min; Yong Wook Jung (Scientific Reports, 2022)
Abstract The aim of this study was to examine the effect of seasonal changes on the incidence of preeclampsia (PE) in South Korea and East Asian populations, and to evaluate the relationship between upper respiratory infection (URI) during pregnancy and the development of PE. This cohort study included women who had singleton births between 2012 and 2018 in South Korea. A total of 548,080 first singleton births were analyzed, and 9311 patients (1.70%) were diagnosed with PE. Multivariate analysis showed that older age (≥ 30 years old), low income, residing in the southern part of South Korea, history of cigarette smoking, heavy drinking, higher body mass index, hypertension, or diabetes mellitus were risk factors for PE. Univariate analysis showed that URI was associated with the incidence of PE (P = 0.0294). However, this association was not statistically significant in the multivariate analysis (aOR 1.01; 95% CI 0.95–1.07). After adjusting for confounding variables, the occurrence of PE was the highest in December (aOR 1.21; 95% CI 1.10–1.34) and lowest in July and August. This study demonstrated that there are seasonal variations in the occurrence of PE in South Korea. Moreover, URI may be associated with the development of PE.